[Fe24Se26]: A Host-Guest Compound with Unique Fe-Se Topology - Valldor, Martin; Boehme, Bodo; Prots, Yurii; Borrmann, Horst; Adler, Peter; Schnelle, Walter; Watier, Yves; Kuo, Chang Yang; Pi, Tun-Wen; Hu, Zhiwei; Felser, Claudia; Tjeng, Liu Hao (Chemistry - A European Journal, 2016)
The novel host-guest compound [Cs6Cl][Fe24Se26] (I4/mmm; a=11.0991(9), c=22.143(2) Å) was obtained by reacting Cs2Se, CsCl, Fe, and Se in closed ampoules. This is the first member of a family of compounds with unique Fe-Se topology, which consists of edge-sharing, extended fused cubane [Fe8Se6Se8/3] blocks that host a guest complex ion, [Cs6Cl]5+. Thus Fe is tetrahedrally coordinated and divalent with strong exchange couplings, which results in an ordered antiferromagnetic state below TN=221 K. At low temperatures, a distribution of hyperfine fields in the Mössbauer spectra suggests a structural distortion or a complex spin structure. With its strong Fe-Se covalency, the compound is close to electronic itinerancy and is, therefore, prone to exhibit tunable properties.
CRIS-Team Scopus Importer:2023-03-20
Keywords: inorganic synthesis; iron; magnetic properties; Mössbauer spectroscopy; X-ray diffraction